2019
DOI: 10.1080/22221751.2019.1625728
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of cell membrane localized NTCP expression in proliferating hepatocytes prevents hepatitis B virus infection

Abstract: Hepatocyte proliferation could result in the loss of covalently closed circular DNA (cccDNA) and the emergence of cccDNA-cleared nascent hepatocytes, which appear refractory to hepatitis B virus (HBV) reinfection with unknown mechanism(s). Sodium taurocholate cotransporting polypeptide (NTCP) is the functional receptor for HBV entry. In this study, down-regulation of cell membrane localized NTCP expression in proliferating hepatocytes was found to prevent HBV infection in HepG2-NTCP-tet cells and in liver-huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…Speci cally, among the 11 key target genes, CCNB1, CDKN1A, EP300, ABL1, CDK4, and CCNA2 are enriched in the cell cycle pathway, and previous studies have shown that the expression of these factors could regulate the cell cycle to varying degrees, promote or inhibit cell proliferation [21][22][23][24][25][26] . Hepatocyte proliferation has been reported to accelerate during HBV infection 27 , leading to the downregulation of NTCP in hepatocytes, which contributes to HBV cccDNA loss and further accelerates HBV clearance 12,28 . Our study suggested that TGYP might exert anti-HBV effects by regulating the cell-cycle-related genes which manipulate hepatocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speci cally, among the 11 key target genes, CCNB1, CDKN1A, EP300, ABL1, CDK4, and CCNA2 are enriched in the cell cycle pathway, and previous studies have shown that the expression of these factors could regulate the cell cycle to varying degrees, promote or inhibit cell proliferation [21][22][23][24][25][26] . Hepatocyte proliferation has been reported to accelerate during HBV infection 27 , leading to the downregulation of NTCP in hepatocytes, which contributes to HBV cccDNA loss and further accelerates HBV clearance 12,28 . Our study suggested that TGYP might exert anti-HBV effects by regulating the cell-cycle-related genes which manipulate hepatocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Results suggested the expression of these key genes were possibly related to the disease status of CHB. Furthermore, CHB patients with signi cant liver in ammation could bene t from improved antiviral effect 12 . To further explore the relationship between key target genes and liver in ammation in CHB patients, we compared the expression of 71 patients with abnormal serum ALT or AST levels (ALT ≄ 40 or AST ≄ 35) and 34 patients with normal serum ALT and AST levels (ALT < 40 and AST < 35).…”
Section: The Molecular Docking Of Key Compounds and Key Target Genesmentioning
confidence: 99%
“…NTCP has a very short half-life of less than 24 h and its expression is rapidly downregulated in isolated primary hepatocytes in vitro [42,43]. This down-regulation is responsible for reduced or blocked HBV infection in long-term cultured primary human hepatocytes and most immortalized human hepatoma cell lines [44]. Therefore, overexpressing human NTCP on these cells is necessary to study HBV infection in vitro [45].…”
Section: Sodium Taurocholate Co-transporting Polypeptide (Ntcp)mentioning
confidence: 99%
“…Notably, the discovery of the sodium taurocholate co-transporting polypeptide (NTCP) as the receptor of HBV has largely advanced our understanding of humoral immune responses and anti-HBV antibodies during chronic HBV infection, which was largely neglected in previous HBV studies ( Yan et al, 2012 ; Ni et al, 2014 ). The NTCP interacts directly with the preS1 domain of the HBV surface antigen (HBsAg), and antibodies against HBsAg could block the virus entry into cells, neutralize the virus, and restrict the spread of HBV ( Wu et al, 2019 ; Yan et al, 2019 ). Thus, antibodies play important roles in limiting HBV infections and eliminating the virus.…”
Section: Introductionmentioning
confidence: 99%